2018
DOI: 10.4081/ejh.2018.2985
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of kynurenic acid and 3-hydroxyanthranilic acid after rat traumatic brain injury

Abstract: Using an immunohistochemical technique, we have studied the distribution of kynuneric acid (KYNA) and 3-hydroxyanthranilic acid (3-HAA) in a rat brain injury model (trauma). The study was carried out inducing a cerebral ablation of the frontal motor cortex. Two mouse monoclonal specific antibodies previously developed by our group directed against KYNA and 3-HAA were used. In control animals (sham-operated), the expression of both KYNA and 3-HAA was not observed. In animals in which the ablation was performed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Histochemistry was used in parallel with molecular techniques as the proper approach to mechanistically explain the molecular basis of different diseases; this special attention to the cellular mechanisms responsible for pathological processes may also explain the progressive decrease of the published articles on basic Cell biology. Consistently with the trend observed in Figure 2 , the papers on Experimental research and medicine have become more numerous: investigations were performed on animals in vivo 70-81 or on cultured cells, 82-89 as experimental systems for human pathologies, to elucidate the effects of the administration of physical or pharmacological agents. The papers on Developmental biology also increased: besides those on embryological development, 90-96 several ones were focussed on stem cells 97-101 and tissue regeneration.…”
Section: How the Articles’ Subjects Changed In A Histochemical Journasupporting
confidence: 62%
“…Histochemistry was used in parallel with molecular techniques as the proper approach to mechanistically explain the molecular basis of different diseases; this special attention to the cellular mechanisms responsible for pathological processes may also explain the progressive decrease of the published articles on basic Cell biology. Consistently with the trend observed in Figure 2 , the papers on Experimental research and medicine have become more numerous: investigations were performed on animals in vivo 70-81 or on cultured cells, 82-89 as experimental systems for human pathologies, to elucidate the effects of the administration of physical or pharmacological agents. The papers on Developmental biology also increased: besides those on embryological development, 90-96 several ones were focussed on stem cells 97-101 and tissue regeneration.…”
Section: How the Articles’ Subjects Changed In A Histochemical Journasupporting
confidence: 62%
“…Previous research has demonstrated that the excreted/secreted products produced during the infection process can alter the host’s immune response ( Duarte et al, 2013 ; Chang et al, 2019 ). Numerous Trp metabolites have regulatory effects on immune cells, 3-HAA at appropriate concentrations has anti-inflammatory activity ( Lee et al, 2016 ), and significant upregulation of 3-HAA has been identified in a rat brain injury model ( Mangas et al, 2018 ). 3-HAA has also been identified as a crucial molecule for vascular Trp regulation in inflammation and lipid metabolism ( Martin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of indoleamine 2,3-dioxygenase-1 and kynureninase were elevated in traumatic brain tissues Mangas et al . [22] found that in the rat TBI models induced by radiofrequency ablation, the kynurenine pathway products of kynurenine and 3-HAA around the lesion significantly increased. In addition, Harper et al .…”
Section: Discussionmentioning
confidence: 99%